What new in diagnostic and therapy type 1 diabetes? Part I - Otto-Buczkowska, Ewa (Przewodnik Lekarza/Guide for GPs, 2011)
Tightening of the diabetes control criteria in the last few years induces searches for adjunctive drugs to reinforce the basic treatment typical of the specific type of the disease. These agents are meant to stimulate insulin secretion, increase insulin sensitivity or inhibit the antagonists of the hormone. Up till now that kind of studies included adults, mainly with type 2 diabetes. Nowadays, however, the increasing number of research focus on type 1 diabetic patients. In recent years more and more frequently the method of multiple daily injections (MDI) of insulin is being replaced by the method of continuous subcutaneous insulin infusion (CSII). It is the most physiological way to administer insulin. Treatment with insulin pumps has been used more frequently in the pediatric patients and in the treatment of diabetes in pregnancy.